(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
This study aims to describe the perception of senior high school students in Probolinggo toward the implementation of English online learning during the coronavirus disease (Covid-19) pandemic according to their personalities. This study used a quantitative descriptive method with a survey as the technique of gathering data. The study utilized online questionnaires on students’ perceptions and students’ personalities and involved 489 respondents from 7 state senior high schools in Probolinggo. The result indicated that the student’s responses were mostly positive toward English online learning. It reached 88% of the respondents who responded positively to the implementation of English online learning. It was found that the students with extroverted personalities contributed more positive responses compared to the introverted students. The positive responses from the extrovert students gained 88% while 79% were the positive response from the introverted personality students.